2019
DOI: 10.1039/c9ra02848j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PVC film pretreatment on performance and lamination of wood-plastic composite plywood

Abstract: This paper investigates the perforation treatment of polyvinylchloride (PVC) plastic films and their plywood composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The result showed that the hot-press time affects the penetration depth of the thermoplastic film. Overpenetration may occur if the hot-press time is too long, which will have a negative impact on the bonding strength of the thermoplastic plywood [22].…”
Section: Dosage Of the Eva Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the hot-press time affects the penetration depth of the thermoplastic film. Overpenetration may occur if the hot-press time is too long, which will have a negative impact on the bonding strength of the thermoplastic plywood [22].…”
Section: Dosage Of the Eva Filmmentioning
confidence: 99%
“…Therefore, accurate control of the secondary press process is a key factor for maintaining the stability of the mechanical mesh structure of the interface layer and the mechanical properties of the panel. A literature search showed that most researchers have systematically studied the hot-press process of thermoplastic plywood [17,22,29,43], but there is no in-depth discussion on the secondary press process. Based on the hot-press process, the effect of the secondary press process on the tensile shear strength of EVA wood-plastic plywood was studied.…”
Section: Effect Of the Secondary Press Process On The Performance Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This method helped to form a more stable “dendritic glue nail” microstructure and contributed to improving the bonding strength and dimensional stability of the PE film-bonded wood-based panel. The perforation of the thermoplastic film was also conducive to increasing the mechanical interlocking between the plastic and wood [ 87 ]. This is because the heat transfer rate was accelerated during the hot pressing.…”
Section: Technical Problems Of Wood-based Panel Made Of Thermoplastic Resin Adhesivementioning
confidence: 99%
“…They considered the properties and possible applications of the WPCs prepared using this method in packaging. Li et al (2019) studied the influence of PVC film perforation pretreatment on the physical and mechanical properties of, and the lamination effect exhibited by, a new WPC to explore and solve the heat transfer problem in the hot-pressing process.…”
Section: Introductionmentioning
confidence: 99%